Health care associated Clostridioidesdifficile infection and colonization in patients admitted at tertiary care hospital Pakistan - Ahmed, Abeera; Aamer Ikram; Nargis Sabir; Gohar Zaman; Adeel Gardezi; Luqman Satti (Journal of the Pakistan Medical Association, 2022)
Objective: To evaluate the epidemiology of clostridioides difficile infections and colonisation in a tertiary-care setting. Method: The cross-sectional study was conducted at the Combined Military Hospital, Rawalpindi, Pakistan, from June 1, 2017, to October 31, 2019, and comprised adult patients admitted in high-risk units of the hospital for any disease experiencing watery stools after 48 hours of hospital admission and passing more than 3 stools per day with no other recognised aetiology. Stool samples of the participants, diagnosed with antibiotic associated diarrhoea, were submitted forglutamate dehydrogenase antigen assay and clostridioides toxin A/B assay detected by enzyme-linked immunosorbent assay and clostridioides difficile toxin gene detection by polymerase chain reaction. Clostridium difficile-associated diarrhoea was diagnosed by a positive toxin assay or polymerase chain reaction. Data was analysed using SPSS25. Results: Of the 715 subjects, 322(45%) were males and 393(55%) were females. The overall mean age was 56.64±8.57 years, and 488(68.3%) were aged <60 years, while 227(31.7%) were aged >60 years. The incidence of clostridioides difficile-associated diarrhoea was found in 10(1.4%) patients and was highest in oncology unit 3(4.3%). No positive case was detected from the high dependency unit and the surgical ward. All the10(1.4%) positive cases were on >2 antibiotics with a combination of oral vancomycin and intravenous metronidazole. Mortality rate was significantly higher in the positive cases compared to those with clostridioides difficile colonisation (p<0.05). Conclusion: The incidence of clostridioides difficile-associated diarrhoea was found to be low. Continues...